Drought reduced monoterpene emissions from the evergreen Mediterranean oak Quercus ilex: results from a throughfall displacement experiment - a.-V. Lavoir; Staudt, M; Schnitzler, J P; Landais, D; Massol, F; Rocheteau, A; Rodriguez, R; Zimmer, I; Rambal, S (Biogeosciences, 2009)
The effects of water limitations on the emission of biogenic volatile organic compounds are not well understood. Experimental approaches studying drought effects in natural conditions are still missing. To address this question, a throughfall displacement experiment was set up in a natural forest of Quercus ilex, an evergreen Mediterranean oak emitting monoterpenes. Mature trees were exposed in 2005 and 2006 either to an additional drought, to irrigation or to natural drought (untreated control). In both years, absolute monoterpene emission rates as well as the respective standard factors of the trees exposed to normal and additional drought strongly declined during the drought periods. Monoterpene emissions were lower in year 2006 than in year 2005 (factor 2) due to a more pronounced summer drought period in this respective year. We observed a signiﬁcant difference between the irrigation and additional drought or control treatment: irrigated trees emitted 82% more monoterpenes during the drought period 2006 than the trees of the other treatments. However, no signiﬁcant effect on monoterpene emission was observed between normal and additional drought treatments, despite a signiﬁcant effect on leaf water potential and photochemical efﬁciency. During the development of drought, monoterpene emissions responded exponentially rather than linearly to decreasing leaf water potential. Emissions rapidly declined when the water potential dropped below −2 MPa and photosynthesis was persistently inhibited. Monoterpene synthase activities measured in vitro showed no clear reduction during the same period. From our results we conclude that drought signiﬁcantly reduces monoterpene ﬂuxes of Mediterranean Holm oak forest into the atmosphere due to a lack of primary substrates coming from photosynthetic processes
Keywords: BVOC emission; Drought; Quercus ilex (voyant); Water availability

Seasonal and annual variation of carbon exchange in an evergreen Mediterranean forest in southern France - ALLARD, V; Ourcival, J M; Rambal, S; Joffre, R; Rocheteau, A (Global Change Biology, 2008)
We present 9 years of eddy covariance measurements made over an evergreen Mediterranean forest in southern France. The goal of this study was to quantify the different components of the carbon (C) cycle, gross primary production (GPP) and ecosystem respiration (Reco), and to assess the effects of climatic variables on these fluxes and on the net ecosystem exchange of carbon dioxide. The Puéchabon forest acted as a net C sink of −254 g C m−2 yr−1, with a GPP of 1275 g C m−2 yr−1 and a Reco of 1021 g C m−2 yr−1. On average, 83% of the net annual C sink occurred between March and June. The effects of exceptional events such the insect-induced partial canopy defoliation that occurred in spring 2005, and the spring droughts of 2005 and 2006 are discussed. A high interannual variability of ecosystem C fluxes during summer and autumn was observed but the resulting effect on the annual net C budget was moderate. Increased severity and/or duration of summer drought under climate change do not appear to have the potential to negatively impact the average C budget of this ecosystem. On the contrary, factors affecting ecosystem functioning (drought and/or defoliation) during March–June period may reduce dramatically the annual C balance of evergreen Mediterranean forests.
Keywords: CO2 fluxes; eddy covariance; Mediterranean ecosystem; Quercus ilex

Summer and winter sensitivity of leaves and xylem to minimum freezing temperatures: a comparison of co-occurring Mediterranean oaks that differ in leaf lifespan. - Cavender-Bares, J; Cortés, P; Rambal, S; Joffre, R; Miles, B; Rocheteau, A (The New phytologist, 2005)
Freezing sensitivity of leaves and xylem was examined in four co-occurring Mediterranean oaks (Quercus spp.) grown in a common garden to determine whether freezing responses of leaves and xylem were coordinated and could be predicted by leaf lifespan. Freezing-induced embolism and loss of photosynthetic function were measured after overnight exposure to a range of subzero temperatures in both summer and winter. Both measures were found to be dependent on minimum freezing temperature and were correlated with leaf lifespan and vessel diameter. The dependence of xylem embolism on minimum freezing temperature may result from the decline in water potential with ice temperature that influences the redistribution of water during freezing and leads to an increase in xylem tension. Winter acclimatization had a relatively small effect on the vulnerability to freezing-induced embolism, although leaf photosynthetic function showed a strong acclimatization response, particularly in the two evergreen species. Quercus ilex, the species with the longest leaf lifespan and narrowest vessel diameters, showed the highest freezing tolerance. This helps explain its ability to inhabit a broad range throughout the Mediterranean region. By contrast, the inability of the deciduous oaks to maintain photosynthetic and vascular function throughout the winter indicates a competitive disadvantage that may prevent them from expanding their ranges.
Keywords: cold acclimatization; decline in F V /F M; freezing-induced embolism; leaf lifespan; minimum temperatures; xylem anatomy